Photodegradation of lincomycin in aqueous solution - Agatino Di Paola; Maurizio Addamo; Vincenzo Augugliaro; Elisa García-López; Vittorio Loddo; Giuseppe Marcì; Leonardo Palmisano (International Journal of Photoenergy)
Aqueous solutions of lincomycin were irradiated with UV light in homogeneous and heterogeneous systems. Lincomycin disappeared in both systems but the presence of TiO2 noticeably accelerated the degradation of the antibiotic in comparison with direct photolysis. The rate of decomposition was dependent on the concentration of lincomycin and followed a pseudo-first-order kinetics. Photolysis involved only the oxidation of lincomycin without mineralization. Differently, the treatment with TiO2 and UV light resulted in a complete mineralization of the antibiotic. The degradation pathways involved S- and N-demethylation and propyldealkylation. The mineralization of the molecule led to the formation of sulfate, ammonium, and nitrate ions.